Design and Validation of an Instrument to Evaluate Digital Competence in First-Year Students of Education Majors from Three Public Universities in Chile [Diseño y Validación de Un Instrumento Para Evaluar Competencia Digital en Estudiantes de Primer Año de Las Carreras de Educación de Tres Universidades Públicas de Chile] - Silva-Quiroz, J; Abricot-Marchant, N (GTE-Educational Technology Group, University of the Balearic Islands, 2022)
Digital competence (DC) is fundamental for the personal and academic development of today s university students. Evaluating the level of DC in the first years of university education of students of pedagogical careers is relevant to introduce improvements in the careers in the area of Education. The general objective of this work was design and validite of the COMPDIG-PED (Digital competency in pedagogy) assessment instrument in a context of careers in the area of education in three Chilean public universities. This article presents the design and validation of a CD assessment instrument called COMPDIG-PED, based on the framework DIGCOMP (Digital Competence) developed by the European Economic Community. Its reliability and construct validity are established, together with the corresponding statistical analyses, having worked on its content validity through expert judgment. The sample consisted of 841 students. The results show that COMPDIG-PED is an instrument that meets the standards for measuring the CD of first year students of pedagogical careers in particular and of any university career in general. © GTE-Educational Technology Group, University of the Balearic Islands. All rights reserved.